Effects of Torrefaction Temperature on the Characteristics of Betung (Dendrocalamus asper) Bamboo Pellets - Bagus Saputra; Karina Gracia Agatha Tambunan; Intan Fajar Suri; Indra Gumay Febryano; Dian Iswandaru; Wahyu Hidayat (The University of Lampung, 2022)
The objective of this study was to evaluate the effects of torrefaction temperature on the physical and mechanical properties of betung bamboo (Dendrocalamus asper) pellets. Torrefaction was conducted in an electric furnace at 200°C, 240°C, and 280°C for 50 minutes. The physical properties evaluated included color change, density, moisture content, water resistance, and water adsorption. The mechanical properties were also investigated by compressive strength test. The result showed that torrefaction affected the color properties of betung bamboo pellets with ∆E values of more than 12 or totally changed. The density and moisture content of torrefaction bamboo betung pellets decreased with increasing torrefaction temperature. The results also showed that the hydrophobic properties of the bamboo betung pellets improved with the increased of torrefaction temperature. The highest compressive strength value was obtained by bamboo betung pellets torrefied at 200°C and the values decreased with the increase of temperature. In conclusion, there were differences in the physical and mechanical properties of bamboo betung pellets that were torrefied at different temperatures. Torrefaction with an electric furnace effectively improved the quality of betung bamboo pellets. Keywords: Bamboo betung, pellets, temperature, torrefaction